Research-based instructional practices of effective principals - Bingham, Charles Steven; Egelson, Paula; Sanzo, Karen (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"Extant literature on evidence-based instructional strategies mediated by elementary and secondary school leaders is surprisingly scant. Seeking to fill the gap, the editors of this book have curated the research and craft knowledge of eminent and emergent practitioner scholars who collectively provide a starting place for aspiring and practicing principals. Each author builds on research-based instructional practice in schools and districts in which they have worked, either as principals or as school-university or service-provider partners. They provide examples, action plans, frameworks, lessons learned, and strategies to successfully develop and implement research-based instruction and supporting structures in schools and classrooms"--